Effects of exercise‐induced dyspnoea on the aspiration rate among patients with acute exacerbation of chronic obstructive pulmonary disease. (20th May 2019) - Liu, Ni; Li, Youxia; Chen, Ping; Wu, Zhida; Hou, Peng; Zheng, Zeguang; Chen, Rongchang
Abstract: Purpose: To use radionuclide imaging to investigate silent aspiration among patients recovering from an acute exacerbation of chronic obstructive pulmonary disease (AECOPD). We also evaluated the effects of exercise‐induced dyspnoea on silent aspiration in COPD patients. Patients and methods: Recovering AECOPD patients admitted to the First Affiliated Hospital of Guangzhou Medical University between December 2013 and December 2015 were selected for the radionuclide aspiration test along with healthy volunteers of similar age. Aspiration‐negative AECOPD patients were randomized into two subgroups. Patients in group A performed symptom‐limited incremental cycle exercise test. Patients in group B were resting on the exercise bicycles. Aspiration‐negative healthy volunteers performed symptom‐limited incremental cycle exercise test (group C). Three groups performed a radionuclide aspiration test 30 min after exercise. Results: The silent aspiration rates among recovering AECOPD patients and healthy volunteers were 44.19% (57/129) and 0 (0/18) ( P = 0.00). The aspiration rates in groups A and B were 33.33% (10/30) and 23.33% (7/30), ( P = 0.39) and groups A and C were 33.33% (10/30) and 0% (0/12), ( P = 0.04). Conclusion: Recovering AECOPD patients had significantly higher silent aspiration rates than healthy volunteers of similar age. The evidence is not strong enough to support the patients with exercise‐induced dyspnoea‐increased aspiration rate.